Treatment of Down Syndrome-Associated Arthritis with JAK Inhibition. (16th July 2022) - Jones, Jordan T.
Abstract : Down syndrome (DS) results from a trisomy of chromosome 21, which causes immune dysregulation that leads to hyperactivation of interferon and Janus kinase (JAK) signaling. This results in complex medical abnormalities in the immune system and an increase in autoimmune and autoinflammatory conditions such as down syndrome-associated arthritis (DA). DA is an aggressive, destructive, inflammatory arthritis that is easily misdiagnosed and difficult to treat. Treatment commonly includes immunosuppressive therapy, but these are often associated with adverse effects and ineffectiveness. This case report outlines a 6-year-old male with DA that was successfully treated with the JAK inhibitor tofacitinib. Due to the aggressive nature of DA and poor response to many immunosuppressive therapies, this case report was created to increase awareness of JAK inhibition as an effective, well-tolerated treatment for DA.